Developing Institutional Repositories in Academic Libraries: Best Practices and Challenges (International Journal of Food and Nutritional Sciences, 2022)
Institutional Repositories (IRs) have emerged as essential components of academic libraries, enabling open access to scholarly output, preserving institutional memory, and enhancing research visibility. This article explores the development and implementation of institutional repositories in academic libraries, with a focus on best practices, technological frameworks, and the challenges faced in different institutional contexts. Through a review of global literature and real-world case studies from India, South Africa, the United States, and Latin America, the study analyzes common success factors and barriers such as policy development, faculty engagement, metadata standards, and sustainability. The paper concludes with practical recommendations for building and managing successful IRs and reflections on their evolving role in digital scholarship.